Retroperitoneal robot-assisted live-donor nephrectomy: A single-center study - Rowaiee, Rashed; Gholami, Mandana; Concepcion, Waldo; Vedayar, Hemant; Janahi, Farhad (Frontiers in Transplantation, 2023)
Background As the demand for kidney transplants continues to increase globally, healthcare institutions face a challenge to bridge the gap between patients waitlisted for kidney transplants and the number of donors. A major factor influencing the donor's decision is the operative risk and potential complications of the surgery. Open surgical approaches have been vastly replaced with laparoscopic donor nephrectomies as the standard of practice. However, there is a growing body of evidence pointing towards its potential superiority over laparoscopic methods. In this study, we aim to present our experience on outcomes of Robotic-Assisted Live Donor Nephrectomies (RALDN), the first series of its kind in the United Arab Emirates (UAE). Methods We retrospectively collected data from patients who underwent RALDN at Mediclinc City Hospital. Demographic data, laboratory investigations, and operative details were collected and analyzed. Results Seven patients underwent RALDN between 2021 and April 2022 at our facility. Four donors were male while three were female. Median length of hospital stay was 4 days. In our study, one of the patients suffered from a Clavien-Dindo grade IV complication which necessitated prolonged admission. Conclusion We conclude that RALDN is a safe method for donor kidney procurement, carrying a low risk of morbidity and mortality. This method could potentially evolve the number of kidney donors to address the issue of high kidney transplant demand.